Urbane Widerstände - Urban Resistance. - (:unkn) unknown (Lang, 2018)
Seit der Jahrtausendwende ist eine Vielzahl von Widerstandsbewegungen in Städten weltweit zu beobachten. Die bekanntesten unter ihnen sind der Arabische Frühling, Occupy Wallstreet, die Bewegung des 15M/Indignados oder die zahlreichen Recht auf Stadt-Bewegungen. Die Widerstandsbewegungen unterscheiden sich in ihren Zielsetzungen, Vorgehensweisen und Manifestationen. Die Beiträge setzen sich mit der Analyse von städtischen Protest- und Widerstandsbewegungen auseinandersetzen. Es interessieren die Gemeinsamkeiten und Unterschiede dieser sozialen Bewegungen sowie die übergeordneten gesellschaftlichen Zusammenhänge, in denen sie sich manifestieren.

Since the turn of the millennium, an increasing number of resistance movements in urban spaces have been observed worldwide. The best known among them are the Arab spring, the Occupy Wallstreet movement, the movement of the 15M/Indignados as well as numerous right to the city initiatives. These resistance practices differ in their goals, approaches and manifestations. The anthology presents articles about urban protest and resistance movements with a variety of different empirical and theoretical research approaches. A special focus lies on the differences and the similarities of these social movements as well as on their larger societal context. The collection of mainly empirical studies assembled in this anthology provides an insightful overview of the current field of research on social and resistance movements in an urban context.
Keywords: Gesellschaftsordnung; Urbanität; Stadtraum; Hausbesetzung; Miethöhe; Sozialbewegung; Widerstand; Protest; Ausgrenzung